ECM1 regulates the resistance of colorectal cancer to 5-FU treatment by modulating apoptotic cell death and epithelial-mesenchymal transition induction - Long, Sirui; Wang, Jie; Weng, Fanbin; Pei, Zhigang; Zhou, Shixian; Sun, Guiyin; Xiang, Debing (Frontiers in Pharmacology, 2022)
5-Fluorouracil (5-FU) chemoresistance is a persistent impediment to the efficient treatment of many types of cancer, yet the molecular mechanisms underlying such resistance remain incompletely understood. Here we found CRC patients resistant to 5-FU treatment exhibited increased extracellular matrix protein 1 (ECM1) expression compared to CRC patients sensitive to this chemotherapeutic agent, and higher levels of ECM1 expression were correlated significantly with shorter overall survival and disease-free survival. 5-FU resistant HCT15 (HCT15/FU) cells expressed significantly higher levels of ECM1 relative to parental HCT15 cells. Changes in ECM1 expression altered the ability of both parental and HCT15/FU cells to tolerate the medication in vitro and in vivo via processes associated with apoptosis and EMT induction. From a mechanistic perspective, knocking down and overexpressing ECM1 in HCT15/FU and HCT15 cell lines inhibited and activated PI3K/AKT/GSK3β signaling, respectively. Accordingly, 5-FU-induced apoptotic activity and EMT phenotype changes were affected by treatment with PI3K/AKT agonists and inhibitors. Together, these data support a model wherein ECM1 regulates CRC resistance to 5-FU via PI3K/AKT/GSK3β pathway-mediated modulation of apoptotic resistance and EMT induction, highlighting ECM1 as a promising target for therapeutic intervention for efforts aimed at overcoming chemoresistance in CRC patients.